Systemic Metabolite Changes in Wild-type C57BL/6 Mice Fed Black Raspberries. (17th February 2017) - Pan, Pan; Skaer, Chad W.; Wang, Hsin-Tzu; Kreiser, Michael A.; Stirdivant, Steven M.; Oshima, Kiyoko; Huang, Yi-Wen; Young, Matthew R.; Wang, Li-Shu
ABSTRACT: Introduction : Freeze-dried black raspberries (BRBs) elicit chemopreventive effects against colorectal cancer in humans and in rodents. The objective of this study was to investigate potential BRB-caused metabolite changes using wild-type (WT) C57BL/6 mice. Methods and results : WT mice were fed either control diet or control diet supplemented with 5% BRBs for 8 wk. A nontargeted metabolomic analysis was conducted on colonic mucosa, liver, and fecal specimens collected from both diet groups. BRBs significantly changed the levels of 41 colonic mucosa metabolites, 40 liver metabolites, and 34 fecal metabolites compared to control diet-fed mice. BRBs reduced 34 lipid metabolites in colonic mucosa and increased levels of amino acids in liver. One metabolite, 3-[3-(sulfooxy) phenyl] propanoic acid, might be a useful biomarker of BRB consumption. In addition, BRB powder was found to contain 30-fold higher levels of linolenate compared to control diets. Consistently, multiple omega-3 polyunsaturated fatty acids (ω-3 PUFAs), including stearidonate, docosapentaenoate (ω-3 DPA), eicosapentaenoate (EPA), and docosahexaenoate (DHA), were significantly elevated in livers of BRB-fed mice. Conclusion : The data from the current study suggest that BRBs produce systemic metabolite changes in multiple tissue matrices, supporting our hypothesis that BRBs may serve as both a chemopreventive agent and a beneficial dietary supplement.